Subcutaneous emphysema and pneumomediastinum after endoscopic transnasal removal of nasopharyngeal angiofibroma - M. S. Kuznetsov; A. V. Voronov; V. V. Dvoryanchikov; D. V. Svistov; A. I. Nikitin (Опухоли головы и шеи)
Introduction. Juvenile nasopharyngeal angiofibroma is a rare, benign, well-vascularized tumor of the skull base characterized by destructive growth. The development of endoscopic techniques and experience of surgeons have enabled the removal of this tumor both at early stages and late stages (advanced disease). Patients may develop various complications in the intraoperative and postoperative periods, including massive bleeding, nasal liquorrhea, facial paresthesia, lacrimal hyposecretion, etc. Air penetration into the subcutaneous fat and mediastinum during endoscopic surgery on the paranasal sinuses is rare. Such complication as subcutaneous emphysema and pneumomediastinum after endoscopic endonasal removal of juvenile nasopharyngeal angiofibroma has not been reported in the literature.Case report. A 19-year-old male patient has undergone endoscopic endonasal removal of juvenile nasopharyngeal angiofibroma. The tamponade was removed within the first 24 h postoperatively. Ten hours after it, the patient developed subcutaneous emphysema and pneumomediastinum triggered by sneezing. The diagnosis was confirmed by computed tomography of the neck and chest. The patient was transferred to the intensive care unit and received conservative treatment (including infusion, antibacterial, and antiinflammatory therapy). The symptoms of subcutaneous emphysema and pneumomediastinum subsided in response to treatment. Follow-up examinations (computed tomography and magnetic resonance imaging) confirmed that the tumor had been completely removed. The patient was discharged in a satisfactory condition.Conclusion. Subcutaneous emphysema and pneumomediastinum are exceedingly rare complications of endoscopic endonasal removal of juvenile nasopharyngeal angiofibroma and are caused by anatomical connection between the parapharyngeal / retropharyngeal spaces and mediastinum. To prevent such complications, it is necessary to keep tampons in the nasal cavity for at least 2 days, as well as to instruct patients after surgery (avoid sneezing with their mouth closed, lifting weights, coughing, and vomiting). The nasoseptal flap used to repair the nasopharyngeal defect after tumor removal also ensures its sealing. Patients with complications should undergo computed tomography of the neck and chest (in case of emergency) and should be transferred to an intensive care unit. Conservative treatment (antibacterial and antiinflammatory therapy) will ensure good results in most patients.